Emission characterization, environmental impact, and control measure of PM2.5 emitted from agricultural crop residue burning in China. (15th April 2017) - Zhang, Hefeng; Hu, Jun; Qi, Yixuan; Li, Chunlin; Chen, Jianmin; Wang, Xinming; He, Jingwei; Wang, Shuxiao; Hao, Jiming; Zhang, Linlin; Zhang, Lijia; Zhang, Yuanxun; et al.
Abstract: Agricultural crop residue burning, including open field burning and burned as household fuel, is a significant emission source of primary fine particulate matter (PM2.5 ) and gaseous precursors of secondary PM2.5 . However, limited information exists on emission characterization, environmental impact, and control measure of PM2.5 emitted from agricultural crop residue burning in China. In this study, laboratory simulation experiments were conducted to characterize emission factors of PM2.5 and PM2.5 -bound chemical compositions from the burning of three typical agricultural crop residues (rice, wheat and corn straw). PM2.5 -bound chemical compositions in our measurements include elemental carbon (EC) and organic carbon (OC), water-soluble ions (WSI), polycyclic aromatic hydrocarbons (PAHs) and alkyl-polycyclic aromatic hydrocarbons (APAHs). Emission factors of PM2.5 and PM2.5 -bound EC, OC, WSI, PAHs and APAHs were 13.1, 1.38, 7.68, 1.40, 0.99 × 10 −3 and 0.20 × 10 −3  g kg −1 for rice straw, 6.2, 0.55, 2.93, 1.53, 0.85 × 10 −3 and 0.22 × 10 −3  g kg −1 for wheat straw, and 10.5, 0.94, 5.93, 1.53, 0.93 × 10 −3 and 0.22 × 10 −3  g kg −1 for corn straw, respectively. PM2.5 emissions from agricultural crop residue burning were estimated to be 1248, 1485, and 1826 Gg in 2003, 2008, and 2013, respectively. Environmental impacts resulted from open field burning of agricultural crop residue, including visibility impairment, air quality degradation (sometimes heavy haze pollution) and adverse health effects, were explored in this study. Furthermore, in order to ensure the attainment of good ambient air quality during the harvest season, some control measures, such as straw returning to soil, power generation, biogas production and animal feed supply etc., were proposed to prohibit open field burning of agricultural crop residue in China. Graphical abstract: Highlights: Emission factors of PM2.5, its precursors and chemical compositions from agricultural crop residue burning were characterized. Emission inventories of primary PM2.5 from agricultural crop residue burning were evaluated. Potential environmental impacts due to agricultural crop residue burning were explored. Effective control measures about agricultural crop residue burning were proposed.